An exploration of stigma towards depression in rural Ireland : a mixed methods study - Kennedy, Conor (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2014)
This research demonstrates that experiencing depression is associated with a perceived expectation of being subject to stigmatisation in rural Ireland. Evidence is presented which suggests core social processes, actioned within this setting and driven by dominant social forces, are conspiring to facilitate the proliferation of this scenario.
Keywords: Nursing and Midwifery, Ph.D.; Ph.D. Trinity College Dublin